Generalized distribution Sechk - A. V. Ausiannikau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Model of generalized law of distribution of Sechk and its researched application in statistical radio engineering. Base attributes and statisticians of distribution are given. Algorithms of point estimation of parameter of shift for known and unknown parameters of scale, and also algorithms of a sequential interval estimation of parameter of shift are resulted.